A simple and rapid method of repeated tie over dressing - Hardeep Singh; Aditya Aggarwal; Rakesh Kumar Khazanchi; Sanjay Mahendru; Vimalendu Brajesh; Sukhdeep Singh; S. Krishnan (Indian Journal of Plastic Surgery)
Tie overdressing is commonly used to secure the graft against the raw surface and prevent loss due to of hematoma or seroma. A conventional tie over dressing with silk sutures, is a useful method of securing the graft to raw area. Refixation is difficult when repeated tie over dressings are needed. We assessed a low cost repeated tie over dressing method using sterile sample collection containers and silk suture threads in eight patients. After the graft is applied on the bed, tie-over stitches are taken, and paraffin gauze is applied over with adequate padding; the tie over sutures are passed through the container and the lid is tightened over it to complete the dressing. The lid can be unscrewed easily at any time to inspect the graft and can be easily reapplied in the outpatient department. The skin graft take in all the patients was complete without any seroma or hematoma. A novel and low-cost tie over dressing that enables simple fixation of the dressing, to maintain proper position of grafts that require repeated fixation is reported here.